Trends and Patterns in Turnaround Strategies: A Bibliometric Perspective and Future Research Agenda - Mufaro Dzingirai; Neeta Baporikar (IGI Global, 2023)
The paper aims to examine the publications on turnaround strategies and identify scientific gaps. Hence, bibliographic couplings of countries, institutions, journals, publications, authors, and co-occurrences of the author keywords were analyzed. Bibliographic methods were employed to examine and visualize the characteristics of the publications with the aid of VOSViewer software. Using 174 articles from the Scopus database, the results revealed that corporate distress, turnaround, organizational decline, turnaround strategies, corporate strategy, financial distress, retrenchment, turnaround strategy, and turnarounds were among the most studied key concepts in this area, The “Journal of Strategy and Management” and “European Management Journal” were the top journals. United States, United Kingdom, and India were the most influential countries. The Fort Hays University and McMurry University were top research institutions. Notably, Huang, Y., Reddy, K.S., and Xie, E. were the most influential authors in this research area. These results will help academicians and practitioners.